2003
DOI: 10.1046/j.1525-1497.2003.20739.x
|View full text |Cite
|
Sign up to set email alerts
|

Interactive faculty development seminars improve the quality of written feedback in ambulatory teaching

Abstract: We performed a pre-post study of the impact of three 90-minute faculty development workshops on written feedback from encounters during an ambulatory internal medicine clerkship. We coded 47 encounters before and 43 after the workshops, involving 9 preceptors and 44 third-year students, using qualitative and semiquantitative methods. Postworkshop, the mean number of feedback statements increased from 2.8 to 3.6 statements ( P = .06); specific ( P = .04), formative ( P = .03), and student skills feedback ( P = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 13 publications
4
38
2
Order By: Relevance
“…As described in the literature, it was generally difficult for the students to collect feedback, on general competencies in particular (Heron 2008). Furthermore, although a balance between positive and negative feedback is generally recommended (Salerno et al 2003), the students indicated that they suffered when they received negative feedback regularly, saying it undermined their self-confidence with a negative impact on reflective writing. In the literature we found different opinions on this topic.…”
Section: Discussionmentioning
confidence: 96%
“…As described in the literature, it was generally difficult for the students to collect feedback, on general competencies in particular (Heron 2008). Furthermore, although a balance between positive and negative feedback is generally recommended (Salerno et al 2003), the students indicated that they suffered when they received negative feedback regularly, saying it undermined their self-confidence with a negative impact on reflective writing. In the literature we found different opinions on this topic.…”
Section: Discussionmentioning
confidence: 96%
“…Relatively little emphasis has been placed on investigating the efficacy of the openended, often underutilised, written feedback elements embedded in such instruments (Lye et al 2001;Salerno et al 2003;Jolly & Boud 2013 (Salerno et al 2003) and as a means of documenting specific clinical learning strengths and difficulties (Lye et al 2001). There may be opportunities to further develop these textual comments to communicate important professional development information for students and clinical supervisors.…”
Section: Introductionmentioning
confidence: 99%
“…3 Previous studies have shown that feedback tends to be nonspecific, is not provided in a timely manner, and does not provide learners with sufficient information to improve their performance. [6][7][8][9] Residents and attendings frequently disagree on the quality and quantity of feedback provided, [10][11][12][13][14][15] with the result that feedback is commonly cited as needing improvement. 16,17 Several studies have examined feedback.…”
mentioning
confidence: 99%